Two-sided asymmetric subduction; implications for tectonomagmatic and metallogenic evolution of the Lut Block, Eastern Iran - Arjmandzadeh, R. (2012)
West directed subduction zones show common characteristics, such as low structural elevation, deep trench, steep slab and a conjugate back-arc basin that are opposite to those of the east directed subduction zones. The tectonomagmatic and metallogenic setting of the Lut Block is still a matter of debate and several hypotheses have been put forward. Despite some authors denying the influence of the operation of Benioff planes, the majority propose that it occurred beneath the Afghan Block, while others consider that oceanic lithosphere was dragged under the Lut Block. Cu-Au porphyry deposits seem to occur in an island arc geotectonic setting during the middle Eocene while Mo-bearing deposits are coincident with the crustal thickening during Oligocene. We introduce new trace element and isotope geochemical data for granitoids and structural evidences testifying the two-sided asymmetric subduction beneath both Afghan and Lut Blocks, with different rates of consumption of oceanic lithosphere.